Retrospecto de lesões radiológicas da cabeça de cães e gatos - Melo, Denise Gomes de [UNESP] (2014)
Head injuries are frequently observed in small animal clinics, and regional anatomical knowledge is extremely important to good clinical and radiographic evaluation. Due to this demand and shortage of compilations of radiographic studies of the various head injuries, a retrospective radiographic study was conducted, reviewing radiographs of 669 dogs and 76 cats, of the file from the Radiology Division of the Veterinary Hospital Governor Laudo Natel (HV) of Faculdade de Ciências Agrárias e Veterinárias, of Universidade Estadual Paulista (FCAV/UNESP), in Jaboticabal, SP, from July 2001 to July 2012. From the same file, were reassessed tomographic images of seven dogs obtained during the period June 2011 to September 2013. The frequency, location and type of head injury were correlated to species, sex, age and breed of animals. The dogs were the most observed, with the mongrel dogs, Poodles and Dobermann the most frequent breeds. In cats, there was a prevalence of mongrel cats. The percentage of males and females was similar and animals with more than eight years of age and 2 years to 7 years and 11 months old were most frequently observed. In dogs, the most common changes were soft tissue swelling without bone involvement, in submandibular area, occipital dysplasia and jaw fractures. In cats, a prevalence of mandibular fractures, soft tissue swelling, without bone involvement, in other regions except the submandibular area and increases radiopacity in the nasal cavity without bone involvement were observed. The frequencies observed in this study are consistent with those described in the literature. We conclude that by performing radiography it is possible to diagnose most bone head injuries, with the exception of brain tumors, that should be evaluated with computed tomography